The curator and the recycler - Qamaruz Zaman, Faridah (Universiti Putra Malaysia Press, 2015)
The bowerbirds of the family Ptilonorhynchida are famous for their elaborate structure which are an important tool in their courtship rituals. The structure is constructed to be a bower (gazebo-like) from twigs. Outside the spacious cavern the bowerbird decorates its lawn with individual clusters of brightly coloured fruits and flowers, iridescent beetles’ wings, shells, and other items that it deems attractive. The whole purpose of this huge effort is to have a space to show off his song and dance in wooing the females. Thus the female bowerbird becomes the judge of his curatorial and courtship skills. The female bowerbird later builds a nest for laying eggs on the trees.